POPULISME POLITIK DAN DUKUNGAN ELEKTORAL DALAM PENERAPAN KEBIJAKAN SUBSIDI PUPUK ERA PRESIDEN JOKO WIDODO - Yudananto Ramadan; Luthfi Makhasin; Ihbar Mursalin; Teuku Muzaffarsyah (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
The issue of fertilizer subsidies extends beyond the technical aspects of budget allocation, distribution methods, and discussions surrounding state food sovereignty. Importantly, the fertilizer subsidy policy is also intertwined with the power dynamics among policy actors, which may encompass political strategies. This study utilizes secondary data sourced from official platforms, including the ministry's website, the Central Bureau of Statistics (BPS), and media reports concerning public statements issued by relevant authorities in both the legislative and executive branches. The findings of this article suggest that the fertilizer subsidy policy serves as a political populism strategy, bolstering political support for Jokowi and the candidates he endorses, particularly to maximize electoral gains in the three provinces with the largest voter populations in Indonesia: East Java, West Java, and Central Java. This is evidenced by the strategic allocation of the fertilizer subsidy budget, which is intensified in the years preceding presidential elections, specifically in 2019 and 2024. Consequently, although farmers are not the sole determinants of the electoral success of Jokowi and Prabowo-Gibran, their significant numbers at both national and local levels in these three provinces render them a crucial demographic to secure.